Simple messages to prevent drowning in open water: guidelines from an International Task Force. (1st March 2011) - Bennett, E; Quan, L; Moran, K
Abstract : Introduction: Globally, many organisations have attempted to prevent drowning associated with aquatic recreation by promoting a plethora of messages. This diversity reflects the multifaceted nature of the drowning problem and the lack of an evidence basis. Our objective was to develop a consensus based set of key, simple generic drowning prevention messages for the general public when recreating in various open water settings. Method: We formed a task force of national experts in drowning prevention that included researchers, life saving, and public health representatives from multiple organisations, countries and continents. The consensus process consisted of structured brainstorming to develop water safety messages for two categories: care of self and the care of others. Boating and organised water sports were not addressed. Messages were prioritised using a modified Delphi technique; each prioritisation round eliminated 50% of the messages. Results: From an original compilation of over 60 messages for each category, the Task Force agreed on eight key messages for each category. Learning swimming and water safety survival skills was the preferred option in both categories. Other strongly supported messages related to swimming with lifeguard supervision, the use of lifejackets, and supervision of others. Discussion: Using a modified Delphi consensus process, a task force developed recommendations of informed and concise messages that promote safe recreational use of open water. It is hoped that these messages will improve the clarity and consistency of communication between drowning prevention organisations and the wide range of communities they serve with the ultimate goal of saving lives.